Allegorical analysis of social life - Mohira Islomova (Proceedings of The ICECRS, 2019)
In the article the influence of the ancient Indian epic on world literature is reflected in the scientific analysis of the reflection of events in public life, interpersonal and social relations through symbolic and figurative characters, allegorical heroes.